Writing Awareness - Gwen Gorzelsky (Journal of the Assembly for Expanded Perspectives on Learning, 2013)
The author argues that, by practicing embodied, metaphoric ethnography, educators can revise their roles in classroom social systems and so pursue the goals of critical pedagogy.
Keywords: Writing; ethnographic research; literate practices; pedagogy